EFEK PENAMBAHAN PREBIOTIK PADA PAKAN BERBASIS BAHAN BAKU LOKAL UNTUK MENINGKATKAN PERTUMBUHAN DAN KECERNAAN PAKAN IKAN NILA Oreochromis niloticus - Achmad Noerkhaerin Putra; Aulia Yuaninda; Syah Banten Anarki; Mas Bayu Syamsunarno; Mustahal Mustahal; Dodi Hermawan; Muhammad Herjayanto (Pusat Unggulan Iptek Ketahanan Pangan Universitas Sultan Ageng Tirtayasa, 2020)
This research was conducted to evaluate the effect of prebiotics addition in feed-based feedstuffs locally on growth and feed digestibility of tilapia. Tilapia (5.19 ± 0.01 g) were reared with a density of 20 fish/container for 45 days. The study consisted of 3 treatments (control, 0.5% prebiotic, 1% prebiotic) with 4 replications.Moringa leaf meal, lamtoro leaf meal and rice bran were used in this study as the local feedstuffs, while the prebiotics used were sweet potato extract. The results showed that the total digestibility and specific growth rate were higher (P<0.05) in prebiotic addition compared to controls. 1% prebiotics treatment showed the best value of protein digestibility (78.24 ± 3.97), specific growth rate (1.57 ± 0.02) and feed efficiency (39.13 ± 0.76) than the other treatments.